2020
DOI: 10.1093/mnras/staa2453
|View full text |Cite
|
Sign up to set email alerts
|

The globular cluster system mass–halo mass relation in the E-MOSAICS simulations

Abstract: Linking globular clusters (GCs) to the assembly of their host galaxies is an overarching goal in GC studies. The inference of tight scaling relations between GC system properties and the mass of both the stellar and dark halo components of their host galaxies are indicative of an intimate physical connection, yet have also raised fundamental questions about how and when GCs form. Specifically, the inferred correlation between the mass of a GC system (MGC) and the dark matter halo mass (Mhalo) of a galaxy has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 63 publications
12
59
0
Order By: Relevance
“…Secondly, we find some evidence that the specific frequency T N changes with redshift, consistent with models suggesting that GC formation is fundamentally a baryonic process that results in relations with host galaxy properties that evolve in the context of hierarchical galaxy formation and evolution (e.g. Kruijssen 2015;Choksi et al 2018;Pfeffer et al 2018;El-Badry et al 2019;Kruijssen et al 2019a;Bastian et al 2020).…”
Section: Scaling Relations Between Gc Subpopulations and Their Host Satellite Progenitor Massessupporting
confidence: 84%
See 3 more Smart Citations
“…Secondly, we find some evidence that the specific frequency T N changes with redshift, consistent with models suggesting that GC formation is fundamentally a baryonic process that results in relations with host galaxy properties that evolve in the context of hierarchical galaxy formation and evolution (e.g. Kruijssen 2015;Choksi et al 2018;Pfeffer et al 2018;El-Badry et al 2019;Kruijssen et al 2019a;Bastian et al 2020).…”
Section: Scaling Relations Between Gc Subpopulations and Their Host Satellite Progenitor Massessupporting
confidence: 84%
“…However, the specific frequencies of the Kraken and Gaia-Enceladus exceed those of galaxies of a similar mass at z = 0, suggesting that the scaling relations between the number of GCs and the host galaxy mass evolve with redshift (e.g. Kruijssen 2015;Choksi & Gnedin 2019;Bastian et al 2020). We propose that the excess can be explained by the continued stellar mass growth of galaxies after z acc .…”
Section: Data Ava I L a B I L I T Ymentioning
confidence: 76%
See 2 more Smart Citations
“…The simulations have also shown their ability to use GCs to predict properties of dwarf galaxies that now cause stellar streams (Hughes et al 2019) and have been shown to reproduce the GC colour-magnitude relation (Usher et al 2018). Another observable reproduced by the E-MOSAICS simulations is the relation between the number of GCs and the host galaxy mass (Kruijssen et al 2019a;Bastian et al 2020). In addition, the simulations have made predictions for future observables regarding the formation environments and initial demographics of GCs, to be tested with JWST and the 30-m class telescopes (Reina-Campos et al 2019;Pfeffer et al 2019a;Keller et al 2020).…”
Section: S I M U L At I O N Smentioning
confidence: 86%